The Digital Doctor is In: Is Artificial Intelligence (AI) Used in Hospitals Today? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2024)
The integration of technology into healthcare has been a continuous process, but few advancements have captured the public imagination—and professional scrut...
Keywords: Drug Discovery; Digital Health; Diagnostics; Artificial Intelligence; Patient Care